Strontium ranelate stimulates the activity of bone-specific alkaline phosphatase: interaction with Zn2+ and Mg2+ - Fernández, Juan Manuel (2014)
Strontium ranelate (SR) is an orally administered and bone-targeting anti-osteoporotic agent that increases osteoblast-mediated bone formation while decreasing osteoclastic bone resorption, and thus reduces the risk of vertebral and femoral bone fractures in postmenopausal women with osteoporosis. Osteoblastic alkaline phosphatase (ALP) is a key enzyme involved in the process of bone formation and osteoid mineralization. In this study we investigated the direct effect of strontium (SR and SrCl$latex ^{_{2}} $further decreased Km in all cases. These direct effects of SR on osteoblastic ALP activity could be indicating an alternative mechanism by which this compound may regulate bone matrix mineralization.